Evaluation of silage diets offered to reindeer calves intended for slaughter. II. Feeding of silage and concentrate from January to March - Nilsson, Anna; Olsson, Ingemar; Lingvall, Per (Rangifer, 1996)
An experiment involving 56 male reindeer calves, with a mean initial live weight of 39 kg (SD=4.6), was undertaken to evaluate the effect of the concentrate:silage ratio on the performance during feeding to slaughter. Forty four of the calves were divided in four groups, two groups each being allotted to diets with low, 60% (LC), or high, 80% (HC) proportions of a commercial pelleted feed. The remaining twelve calves were slaughtered at the start of the experiment. The experimenral period lasted from January to March. The proportions of concentrate to silage were based on the dry matter (DM) content. The silage, 44% DM, was made from the primary growth of a predominantly grass sward preserved as plastic-wrapped big bales. Animal health was good throughour the experimenr. Small amounts of lichens were mixed into the diets during the first rwo weeks of feeding and may have contributed to the lack of adapta-tionai problems. The mean daily intakes of DM and metabolisable energy were higher (P<0.01) for calves offered the HC-diet. Despite the higher feed intakes, the increased proportion of concentrate in the diet did not significantly alter live weight gains or carcass weight gains. However, the greater fat deposition (P<0.05) and better carcass gradings indicated a better condition of the animals at slaughtet when less silage was fed. This experiment was the the final part of a three year study of silage based diets for reindeer intended for slaughter and the general conclusion is that the best role of grass silage of this quality is as a limited part of the ration. The silage may, however, play an important role during the adaptation period and further detailed studies are needed to evaluate the applicability of silage as a part of the diet to reindeer.